Reviews of environmental contamination and toxicology, Volume 227 - Whitacre, David M. (Reviews of Environmental Contamination and Toxicology, Continuation of Residue Reviews, 2014)
CONTENTS Foreword Preface Occurrence, Degradation and Effect of Polymer Based Materials in the Environment Scott Lambert, Chris Sinclair, and Alistair Boxall Effects of Addictive Substances During Pregnancy and Infancy and their Analysis in Biological Material Justyna Płotka , Sylwia Narkowicz, Żaneta Polkowska, Marek Biziuk, Jacek Namieśnik Genetic Structure and Diversity of Animal Populations Exposed to Metal Pollution Patricia Mussali-Galante, Efraín Tovar-Sánchez, Mahara Valverde and Emilio Rojas Bioamplification as a Bioaccumulation Mechanism for Persistent Organic Pollutants (POPs) in Wildlife Jennifer M. Daley,  Gordon Paterson, Ken G. Drouillard Index